Rangeland Ecosystem Service Markets: Panacea or Wicked Problem? - Roche, Leslie M.; Saitone, Tina L.; Tate, Kenneth W. (Frontiers in Sustainable Food Systems, 2021)
Rangelands support nearly one-third of Earth’s population and provide a multitude of ecosystem services. Land managers and society face increasing pressures to sustainably intensify rangeland food systems; therefore, the time is ripe for thoughtful approaches to simultaneously produce more food, provide economic opportunities for livestock-dependent communities, and enhance environmental benefits from rangeland ecosystems. Payments for ecosystem services (PES) programs have been put forth as potential mechanisms to maintain the quality and quantity of ecosystem services while enhancing economic viability of livestock operations. Free markets have long been proposed as solutions for mitigating trade-offs from ecosystem services that are not co-produced with livestock production; such markets have failed to emerge at the scale required to address global threats to sustainability. We highlight fundamental obstacles on demand and supply sides that challenge the concept of a market as a panacea; we do so through an interdisciplinary lens of fundamental economic underpinnings overlaid with a social survey of cattle producers’ perspectives. Relevant to the demand side, we discuss the most significant impediments to development and function of non-bundled ecosystem service markets; on the supply side, we provide unique perspectives, using novel interview data from California rangeland cattle producers. Producer interviews highlighted substantial financial challenges threatening the economic sustainability of their operations. Among interviewed producers, 85% identified government regulations as the central threat to their livelihoods. Producers identified opportunities for enhancing enterprise sustainability via improved value and marketing of livestock goods co-produced with ecosystem services, participation in conservation easements, and improved connections with society. Only 11% of producers identified PES programs as future opportunities. When asked about willingness to participate in PES markets, 13% of interviewees indicated they would not, 45% were neutral, and 42% indicated they would consider participating. Interviewees stated trust in the market broker is key and they would be less willing to participate if there was government involvement. Ecosystem service markets – whether voluntary or non-voluntary– are likely not sustainable solutions to the complex social-economic-ecological dilemma ranchers and society face. Sustainability on working rangelands will require partnerships to co-develop strategies to build more equitable food systems and sustain these ecosystems.